Optimization of the preparation process of compound Panax ginseng cream and its in vitro whitening effects - TANG Panpan; CUI Chengbi; JIANG Xin; QI Xin (Shipin yu jixie)
ObjectiveThis study aimed to optimize the production process of composite red ginseng cream to enhance its whitening effects.MethodsThe preparation process conditions of the composite Panax ginseng cream were optimized using orthogonal tests, assessing active ingredient content, antioxidant capacity, tyrosinase inhibition, and suppression of melanin production in B16 mouse melanoma cells.ResultsThe optimal conditions for preparing the composite red ginseng cream were material-liquid ratio 1∶6 (g/mL), inoculation of lactic acid bacteria 1%, and fermentation at 37 ℃ for 2 d. Under the control of these conditions, the cream contained 15.5 mg/g of total saponins, 8.2 mg/g of total flavonoids, and 331.5 mg/g of polysaccharides.The IC50 values for DPPH free radicals, ABTS free radicals, and PTIO free radicals were 561.5, 423.1, and 512.1 μg/mL, respectively. While the IC50 values for inhibiting tyrosinase activity and melanin production in B16 mouse melanoma cells were 721.2 and 497.2 μg/mL, respectively.ConclusionThe optimized preparation of red ginseng cream, using a material-liquid ratio of 1∶6 (g/mL), 1% lactic acid bacteria, and 2 d fermentation at 37 ℃, achieved effective whitening properties through antioxidant and melanin-inhibitory actions.